Publishing & the Book in Africa: A Literature Review for 2016 - Zell, Hans (My University, 2019)
This is the second in a series of annual reviews of select new literature in English that has appeared on the topic of publishing and book development in sub-Saharan Africa. The previous annual literature review, for the 2015 period, can be found at https://www.academia.edu/20432811/Publishing_and_the_Book_in_Africa_- _A_Literature_Review_for_2015. (Print version published in The African Book Publishing Record 42, Issue 1 (March 2016): 11-37 https://doi.org/10.1515/abpr-2016-0003.) Extensively annotated and/or with abstracts, the present list brings together new literature published during the course of 2016, a total of 164 items. Also included are a small number of articles and other documents published in 2015 or earlier, and which have not hitherto been included in the Publishing, Books & Reading in Sub-Saharan Africa online database (see also below). The literature review covers books, chapters in books and edited collections, journal articles, Internet documents and reports, theses and dissertations, interviews, audio/video recordings and podcasts, as well as a number of blog postings, with their posting dates indicated. Newspaper articles are not generally included, unless of substantial length or of special significance. Records are grouped under a range of regional/country and topic-specific headings. It should be noted that, for the most part, literature on particular topics, e.g. children’s book publishing, copyright, educational and schoolbook publishing, digital publishing, reading culture and reading promotion, etc. is listed under topic/subject rather than country headings. However, in the absence of a country index you can search for all country-specific records by using the Ctrl+F ‘find’ function in this document. For example, typing in ‘Ghana’ in the search box will find any text/records (in titles of articles, blog postings and other documents, or if part of the annotations) containing the word Ghana. For more information on scope and type of material covered, consult the introductory pages (print or online) of Publishing, Books & Reading in Sub-Saharan Africa: A Critical Bibliography at http://www.hanszell.co.uk/pbrssa/intro.shtml.
Keywords: Africa; African studies; Bibliography; Reference; Scholarly communication